2018
DOI: 10.31224/osf.io/4rqxc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrashort-Pulsed Laser Machining of Dental Ceramic Implants

Abstract: A novel approach for machining of cylindrical hard materials and arbitrary shapes is presented. Alumina-toughened zirconia dental implants with complex geometry are manufactured with femtosecond quasi-tangential laser ablation. This rapid-prototyping approach for small-scale production decreases the development-time cycle tremendously and trumps conventional approaches. Moreover, a competitive parameter study for radial and tangential ablation with single and multi-pulse is presented. A process achieving an a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Copper foils (0.3 mm, 20 mm x 20 mm) were processed using ultra-short pulsed laser ablation 34,35 to impose geometry and chemical composition. The modified copper oxide electrode (2.25 cm 2 ) comprised ca.…”
Section: Microstructuring Characterization and Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper foils (0.3 mm, 20 mm x 20 mm) were processed using ultra-short pulsed laser ablation 34,35 to impose geometry and chemical composition. The modified copper oxide electrode (2.25 cm 2 ) comprised ca.…”
Section: Microstructuring Characterization and Modellingmentioning
confidence: 99%
“…This set of techniques has been demonstrated through lithographic approaches to gather insights into the formation and nature of active sites in multicomponent systems 31,32 and into the operation of bifunctional catalysts. 33 In this study we identified ultra-short pulsed (USP, pulse duration from fs to ps) laser ablation 34,35 as the technique of choice for the development of model copper electrodes. Whereas nanosecond pulsed laser ablation is a well-established technique for nanoparticle synthesis, 36 USP laser ablation has only found application in the field of catalysis to enhance electrode roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low damage of the substrate below the absorbing and ablated material, structural modification and ablation of hard-to-machine and heat-sensitive materials is feasible. These include ceramics like alumina, zirconia [3][4][5], or glass [6,7]. In addition, the machining of diamond and cubic boron nitride without phase transition is possible [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Combining laser beams with high quality, different optical configurations, and the possibilities of combining the control of the laser with 5-or 7-axis machines, it is possible to define protocols to machine samples with very different 3D shapes. 21,22 Also an adequate combination of focusing lenses allows to machining the inner surface of pieces with complex shapes, for instance, calibers with high aspect ratios. 23 Data obtained from the clinic regarding the survival rates of all-ceramic materials reveal that their restoration is susceptible to breakage due to repeated occlusal loading.…”
Section: Introductionmentioning
confidence: 99%
“…Laser technologies are evolving very fast and new opportunities are opening to apply them not only in planar samples but also in samples with complex geometries. Combining laser beams with high quality, different optical configurations, and the possibilities of combining the control of the laser with 5‐ or 7‐axis machines, it is possible to define protocols to machine samples with very different 3D shapes 21,22 . Also an adequate combination of focusing lenses allows to machining the inner surface of pieces with complex shapes, for instance, calibers with high aspect ratios 23 …”
Section: Introductionmentioning
confidence: 99%